Investigation of plasma filter Influence on lons charge state of Dc vacuum arc plasma; 7th International Conference on Modification of Materials with Particle Beams and Plasma Flows (Tomsk, Russia, 25-30 July 2004) - Sinebryukhov A. A.; Dektyarev S. V. Sergey Valentinovich; Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich (2004, 2004)
At present time the Vacuum Arc Plasma Generators (VAPG) by the materials modification(plasma sputtering, ion implantation etc.) are most widely used. It is necessary to know therelative densities of the ions with various charge state in order to understand the obtained results and to choose treatment modes choice. The presented work is dedicated to the investigation of the influence of the shutter type plasma filter (PF), designed in Nuclear Physics Institute, on the charge state generated by the DC vacuum arc plasma.The investigations have been made using a new approach to the time-of-flight method realization. The experiments have been performed with cathodes of various types - both monopropellant and composite. The plasma charge state has been investigated with plasma filter operating both in passive and active modes. The influence of the plasma filter operation modes (PF with magnetic field, PF with magnetic field and bias potential and passive PF) on the plasma ions charge state for various cathode materials has been detected. The possible mechanisms of charge state changing have been discussed